2013
DOI: 10.4236/jmp.2013.42022
|View full text |Cite
|
Sign up to set email alerts
|

Decaying of Nitrogen Second Positive System by Addition of H<sub>2</sub> Gas in Air DB Discharge

Abstract: Effects of addition of H 2 gas in air DB discharge on its optical and electrical characteristics have been studied. Optical emission spectroscopy is used to investigate the effect of hydrogen admixing on the emission intensity of the nitrogen second positive systems (300 -420 nm) and the relative population density of   3 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…At 90%He and 10%H 2 , all peaks of He species were clearly detected at 336, 356, 388, 501, 587, 667, 706 and 727.5 nm while only one peak of H 2 species appeared which was H α at 656.3 nm representing hydrogen atom excitation. This was related to the characteristic of cold plasma presented in the study of El-Zeer et al 49 and mentioned in Yepez et al 46 ’s work that cold plasma consisted mostly of hydrogen radicals responding in the reaction. For the case of 20%He and 80%H 2 , the plasma color was visually observed to became brighter/lighter, having a more whitish tone as shown in supplementary materials Fig.…”
Section: Resultsmentioning
confidence: 75%
“…At 90%He and 10%H 2 , all peaks of He species were clearly detected at 336, 356, 388, 501, 587, 667, 706 and 727.5 nm while only one peak of H 2 species appeared which was H α at 656.3 nm representing hydrogen atom excitation. This was related to the characteristic of cold plasma presented in the study of El-Zeer et al 49 and mentioned in Yepez et al 46 ’s work that cold plasma consisted mostly of hydrogen radicals responding in the reaction. For the case of 20%He and 80%H 2 , the plasma color was visually observed to became brighter/lighter, having a more whitish tone as shown in supplementary materials Fig.…”
Section: Resultsmentioning
confidence: 75%
“…An increase in saturated and a decrease in unsaturated fatty acids were observed in all treated samples. Solid fractions had higher exposure to reactive plasma species (especially H radicals and H + ) (El‐Zeer et al, 2013) and showed more considerable changes in their composition. A significant increase in stearic acid (18:0) was observed in solid fractions from 4.5% to 10.4%.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that HVACP can degrade the H 2 molecules forming H + , H 3 + , and H ● species by 0.0001%, 0.1%, and 1%, respectively (El‐Zeer et al, 2013). As the H ● radicals are more abundant in the process, it can be suggested that H ● radicals are the most active species and can be responsible for any possible reaction.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that HVACP can degrade the H 2 molecules forming H + , H 3 + , and H * species by 0.0001%, 0.1%, and 1 %, respectively (El-Zeer et al, 2013). Since the H * radicals are more abundant in the process, it can be suggested that H * radicals are the most active species and can be responsible for any possible reaction.…”
Section: Fig 2 -About Herementioning
confidence: 99%